2015
DOI: 10.1177/1753193415613583
|View full text |Cite
|
Sign up to set email alerts
|

Defining postoperative stability in children with radial polydactyly

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…However, we found an inconsistent definition of instability. We agree with the criteria of MCP stability as defined by Engelhardt et al (2016) and would add that stability should be assessed both in extension and 30 of flexion and should account for malalignment at rest. Furthermore, a significant variability in physiological laxity (Engelhardt et al, 2016) must be considered.…”
Section: Discussionsupporting
confidence: 67%
“…However, we found an inconsistent definition of instability. We agree with the criteria of MCP stability as defined by Engelhardt et al (2016) and would add that stability should be assessed both in extension and 30 of flexion and should account for malalignment at rest. Furthermore, a significant variability in physiological laxity (Engelhardt et al, 2016) must be considered.…”
Section: Discussionsupporting
confidence: 67%
“…In our study, all the joint deviations were measured with the hands in a relaxed state rather than a passive one. Engelhardt et al (2015) reported that passive ulnar or radial deviation of 30° or less should be regarded as physiological in children. All of the distal deviation angles were greater than 30° in our study.…”
Section: Discussionmentioning
confidence: 99%
“…All the joints deviations were measured with relaxed hands, rather than a passive state. Engelhardt et al reported that any passive ulnar deviation or radial deviation up to 30° should be regarded as physiological in children (Engelhardt et al, 2016).…”
Section: Discussionmentioning
confidence: 99%